Assessment of optimal insulin administration timing for standard carbohydrates‐rich meals using continuous glucose monitoring in children with type 1 diabetes: A cross‐over randomized study. Issue 5 (18th May 2019) - Tucholski, Krzysztof; Sokołowska, Magdalena; Tucholska, Dagmara; Kamińska, Halla; Jarosz‐Chobot, Przemysława
Abstract: Aims/Introduction: The present study was an assessment of postprandial glucose concentration after carbohydrates‐rich meals using continuous glucose monitoring in 30 children with type 1 diabetes treated using continuous subcutaneous insulin infusion with a rapid‐acting insulin analog. Materials and Methods: Over a period of 3 days, participants administered simple boluses with different delay times between insulin administration and the beginning of carbohydrates‐rich meal consumption (meal no. 1 containing 197 kcal, no. 2 containing 247 kcal and meal no. 3 containing 323 kcal; containing practically no protein and fat). In the present cross‐over randomized study, we analyzed the average glucose concentration profiles in 5‐min intervals, mean glucose at insulin administration, mean glucose after 120 and 180 min, mean and peak glucose, glucose peak time, areas under the glucose and glucose increase curves, and time period lengths with glucose <50, 70 mg/dL, and >140 and 200 mg/dL. Results: For test meals at 20‐min versus 0‐min delay time, the study exposed a longer median time period to reach peak glucose (95 vs 65 min, P  = 0.01) after meals. A tendency to the lowest peak and mean glucose, and the longest time with glucose within a normal range was observed in patients who administered bolus insulin 20 min before a meal. Conclusions: For carbohydrates‐rich meals, administration of a proper dose of a rapid‐acting insulin analog is crucial. The influence of rapid‐acting insulin analog administration timing seems to be of minor importance in comparison with correct insulin dose adjustment; however, a tendency to achieve more balanced glucose profiles was found in a group who administered insulin 20 min before a meal. Abstract : In our cross‐over randomized study, we analyzed the assessment of postprandial glucose concentration after three different carbohydrates‐rich meals using continuous glucose monitoring in 30 children with type 1 diabetes treated using continuous subcutaneous insulin infusion with a rapid‐acting insulin analogs. We discovered that for carbohydrates‐rich test meals, administration of a proper dose of a rapid‐acting insulin analog is crucial. The influence of rapid‐acting insulin analog administration timing seems to be of minor importance in comparison with correct insulin dose adjustment; however, a tendency to achieve more balanced glucose profiles was found in a group who administered insulin 20 min before a meal.